3D cryoimaging of cell-mediated cholesterol crystal clearance in human atherosclerotic lesions - Jenny Capua-Shenkar; Antonia Kaestner; Katya Rechav; Vlad Brumfeld; Ifat Kaplan-Ashiri; Neta Varsano; Ori Avinoam; Chen Speter; Moshe Halak; Howard Kruth; Lia Addadi (Proceedings of the National Academy of Sciences, 2025)
We applied micro-computed tomography, high-resolution cryo-scanning electron microscopy (SEM) combined with cathodoluminescence, and cryo-focused ion beam Milling-SEM to perform three-dimensional imaging of human atherosclerotic tissues with tens of nanometers resolution, under hydrated, near-native conditions with minimal sample processing. The same technology was applied to cultured macrophages exposed to cholesterol crystals, and the observations made on the macrophages were compared to those made on the pathological tissue. We observed that cholesterol crystal digestion and, eventually, cholesterol crystal clearance occurs in the advanced human plaques through cellular processing. Our findings suggest that cholesterol crystal disassembly occurs through the esterification of crystalline cholesterol to cholesteryl-ester in isolated volumes, whereby the ester aggregates into intra- and extracellular pools. The hypothesis is supported by the close similarity of the processes imaged in the human tissue and in the macrophages and is in agreement with earlier biochemical studies performed on cultured macrophages.